Maindam Stability Analysis of Retarding Basin TR-01 Flood Control Project Das Sanggai 1A Advanced KIPP IKN Region East Kalimantan - Husain, Sayid Agil; Azikin, Busthan (CV Insight Publisher, 2025)
Infrastructure development on KIPP-IKN East Kalimantan area faces challenges such as flooding and unavailability of raw water. To address these issues, a Retarding basin is being built to address these issues. However, the engineering geological conditions on the basin and surrounding area can vary significantly, impacting the construction process. Further research is needed to understand these conditions and safety factors for slope stability and seepage in the main dam building. The research method used is the surface and subsurface geological mapping method to analyze engineering geological conditions as well as simulating the stability of the main dam using data from laboratory analysis. The research area consists of residual soil classified as Class D and mudstone as Class Middle, with fair-poor quality rocks. Slope stability simulations show that the area meets minimum requirements and is safe from landslides. Additionally, seepage stability simulations show that the TR-01 retarding basin's seepage discharge is below maximum permitted discharge requirements and is included in the safe category.